To solve this system, we can use the method of substitution.
First, let's solve for y in terms of x in the first equation:
y = -2x + 8
Next, substitute this expression for y in the second equation:
3x - 4(-2x + 8) = 12
Simplify the equation:
3x + 8x - 32 = 12
11x - 32 = 12
Move the constant term to the other side:
11x = 12 + 32
11x = 44
Divide both sides by 11:
x = 44/11
x = 4
Now, substitute this value of x back into the first equation to solve for y:
y = -2(4) + 8
y = -8 + 8
y = 0
Therefore, the solution to the linear system is x = 4 and y = 0.
Solve the linear system: y= -2x+8
3x-4y=12
1 answer